Simulation of dynamic processes in spherical and cylindrical shells - Kuropatenko, Valentin Fedorovich; Andreyev, Yuriy Nikolaevich (Computational Continuum Mechanics, 2010)
Differences between the results obtained in the numerical simulation of dynamic processes that occur in continua and the results obtained in physical experiments come from an error of three types: an error in the physical model (∆Ph), an error in the mathematical model (∆M), and a measurement error (∆m). The paper focuses on the comparison of ∆Mand ∆Phсonsidering a medium placed in a spherically symmetric shell as an example. It is shown that within a certain velocity range the energy dissipation defined by an error in a finite-difference approximation may exceed the energy dissipation generated by a perfect plasticity model.
Keywords: mathematical modeling; difference scheme; entropy generation; von Neumann-Richtmyer viscosity; Kuropatenko method; converging and diverging shells; perfect plasticity